Systemic Inflammation and the Increased Risk of Inflamm-Aging and Age-Associated Diseases in People Living With HIV on Long Term Suppressive Antiretroviral Therapy - Babu, Hemalatha; Ambikan, Anoop T.; Gabriel, Erin E.; Svensson Akusjärvi, Sara; Palaniappan, Alangudi Natarajan; Sundaraj, Vijila; Mupanni, Naveen Reddy; Sperk, Maike; Cheedarla, Narayanaiah; Sridhar, Rathinam; Tripathy, Srikanth P.; Nowak, Piotr; et al. (Frontiers in Immunology, 2019)
The ART program in low- and middle-income countries (LMIC) like India, has a public health approach with the standardized regimen for all people living with HIV (PLHIV). Based on the evidence from high-income countries (HIC), the risk of an enhanced and accentuated onset of premature-aging or age-related diseases has been observed in PLHIV. However, very limited data is available on residual inflammation and immune activation in the populations who are on first-generation anti-HIV drugs like zidovudine and lamivudine that have more toxic side effects. Therefore, the aim of the present study was to evaluate the levels of systemic inflammation and understand the risk of age-associated diseases in PLHIV on long-term suppressive ART using a large number of biomarkers of the inflammation and immune activation. Blood samples were obtained from therapy naïve PLHIV (Pre-ART, n=43), PLHIV on ART for >5 years (ART, n=53), and HIV-negative healthy controls (HIVNC, n=41). Samples were analyzed for 92 markers of inflammation, sCD14, sCD163, and telomere length. Several statistical tests were performed to compare the groups under study. Multivariate linear regression was used to investigate the associations. Despite a median duration of eight years of successful ART, sCD14 (p<0.001) and sCD163 (p=0.04) levels continued to be significantly elevated in ART group as compared to HIVNC. Eleven inflammatory markers, including 4E-BP1, ADA, CCL23, CD5, CD8A, CST5, MMP1, NT3, SLAMF1, TRAIL and TRANCE, were found to be significantly different (p<0.05) between the groups. Many of these markers are associated with age-related co-morbidities including cardiovascular disease, neurocognitive decline and some of these markers are being reported for the first time in the context of HIV-induced inflammation. Linear regression analysis showed a significant negative association between HIV-1-positivity and telomere length (p<0.0001). In ART-group CXCL1 (p=0.048) and TGF- (p=0.026) have a significant association with increased telomere length and IL-10RA was significantly associated with decreased telomere length (p=0.042). This observation warrants further mechanistic studies to generate evidence to highlight the need for enhanced treatment monitoring and special interventions in HIV-infected individuals.